Hybrid Model for Secure Communications and Identity Management in Vehicular Ad Hoc Networks - Gonçalves, Fábio Raul Costa (2017)
Intelligent Transportation Systems (ITS) is a set of applications and services that aim to make driving easier, more comfortable and secure, without neglecting user privacy. Vehicular Ad hoc Networks (VANETs) enable the several nodes to communicate between them. These have a very specific set of characteristics, which makes them very challenging, particularly in terms of security.This paper presents an hybrid security model for VANETs and the results taken from its performance evaluation. This hybrid security model relies on Public Key Infrastructure (PKI) and Attribute Based Encryption (ABE) plus Identity Manager (IdM) and has been called VPKIbrID; It combines these technologies, which complement each other, in order to fulfill all major VANET's security requirements.Performance evaluation of the proposed security model was accomplished through a Java implementation, where the elapsed time of each operation was measured. The analysis of VPKIbrID allowed to conclude that PKI operations are more lightweight hut, when the number of vehicles increases (in a broadcast for example), their performance degrades. ABE operations, maintain the same performance despite the number of vehicles. These are heavyweight, but its performance can be improved by using a key caching mechanism. The cryptographic material needed introduces some overhead, which is more noticeable in the methods using PKI (due to the need of sending the certificate in the message). Using ABE with MAC signatures reduces message overhead to less than half.